Pengaruh Relasi Berorganisasi Terhadap Kualitas Diri Mahasiswa Fakultas Ekonomi Universitas Singaperbangsa Karawang - Khensa Aqilla Haryanto; Muhammad Arif Irsyaad Kurniawan; Risma Sukmawati; Rofrilia Riestiana; Rysna Setia Yuliandri (Peneliti.net, 2023)
This article or piece of writing investigates the relationship between relationships and organizations and student self-worth. The issue is concentrated on the organized relationships between the caliber of students at the University of Singapore's Karawang's Faculty of Economics. The findings based on the data collection through the distribution of questionnaires to the participants, the theoretical references from various sources related to the discussion of this research, and the qualitative analysis and presentation of three variables made up of relationships, organization, and self-quality were used to solve this problem. Based on the findings of this study, it was determined that organized connections have a significant impact on students' levels of self-esteem.